Attachment-oriented endoscopic surgical management for inverted papillomas in the nasal cavity and paranasal sinuses. Issue 5 (October 2019) - Makihara, Seiichiro; Kariya, Shin; Naito, Tomoyuki; Uraguchi, Kensuke; Matsumoto, Junya; Noda, Yohei; Okano, Mitsuhiro; Nishizaki, Kazunori
Abstract: Objective: The treatment of all forms of sinonasal inverted papilloma (IP) is a complete, wide, local resection. The main surgical purpose is to remove all diseased mucosa and mucoperiosteum, together with a cuff of normal-looking mucosa at the attachment site, followed by drilling and/or coagulation. Our aim is to present our experiences in endoscopic surgical management of IP by using attachment-oriented excision. Methods: We present 20 cases of sinonasal IP. The data collected includes the histopathological diagnosis, staging, extension of the tumor, tumor attachment site, approach to surgery, serum squamous cell carcinoma antigen (SCCA) level, and recurrences. Results: All patients underwent endoscopic surgery. A Caldwell-Luc operation was required in addition to the endoscopic surgery in one case. There was one case of recurrence (5%). After the additional operation, there was no recurrence. The tumor attachment sites vary, and the case of recurrence had a wide attachment site at the primary surgery. No major intra- or post-operative complications were observed. Conclusion: The present study shows that attachment-oriented excision for IP is useful for complete resection of IP. Surgeons should choose the surgical approach according to the location of the tumor attachment site rather than the Krouse staging system.